Analysis of change in knowledge, attitude, and practices about COVID-19 following and awareness session in rural population of Western India - Saurabh N Shah; Drashti Shah; Nimisha Desai; Sandip H Shah; Shreyasee Bhowmick (Industrial Psychiatry Journal, 2021)
Background: Beginning of the pandemic showed our limitations in our understanding of the spread of the dreaded coronavirus-19 that had sprung from China and spread through thick and thin across the world. The measures to contain the spread of virus in the absence of specific treatment protocol had everyone grope for the solutions in a very short time frame. One such is the knowledge, attitude, and practice in the rural setup. Aim: The aim of the study is to measure the change in knowledge, attitude, and practices (KAP) regarding COVID-19 following an awareness session in rural population. Materials and Methods: A cross-section interventional study was carried out in January 2021. An interactive awareness session was conducted with the help of audiovisual aids following MOHFW guidelines for COVID-19, and the change in KAP about COVID-19 was measured by pre- and posttest standardized questionnaire. Results: Of all the participants, statistically significant change in knowledge was seen from 43% to 52%. The villagers were educated about preventive steps and a positive change was measured in the practice of changing masks regularly (84%–100%), maintaining social distancing (44%–64%), frequent handwashing (52%–64%). No change was seen in wearing of masks (92%) and negative change was seen in avoiding handshakes (32%–28%). The preventive practices regarding COVID-19 pandemic changed significantly from 50% to 58%. Our study measured positive attitude change toward getting vaccinated from 64% to 72%. Conclusion: A single, short awareness session led to significant change in KAP about COVID-19 in rural population.